Одоление: стихи / Виталий Ложкин - Ложкин Виталий Артемьевич (Сарапульская городская типография, 2006)
Экземпляры: Аб (20160412) / Инвентарный номер: 104045 / Цена: 20.00 / Авт.знак: Л 71 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6